1976
DOI: 10.1111/j.1699-0463.1976.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Porcine Nephropathy: Changes of Renal Function and Structure Perorally Induced by Crystalline Ochratoxin A

Abstract: Experimental porcine nephropathy: Changes of renal function and structure perorally induced by crystalline ochratoxin A. Acta path. microbiol. scand. Sect. A, 84: 429-434, 1976. Nine pigs were fed crystalline ochratoxin A in amounts corresponding to a feed level of 1 mg per kg for 3 months. The only observable lesion developed was a kidney damage, identical to the naturally occurring porcine nephropathy. The changes of renal function was characterized by impairment of proximal tubular function, indicated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 4 publications
7
62
0
Order By: Relevance
“…The amount of OTA in South African feeds (70-80 μg/ kg) from farms with nephropathy problems was significantly less than that presented as the explanation for Danish mycotoxic porcine nephropathy (MPN) (Krogh 1976;Krogh et al 1974). It seems, therefore, that South African porcine nephropathy may have a multitoxic aetiology because it cannot be explained by the concentration of OTA alone, and the conventional explanation appropriate for northern latitudes does not seem to apply.…”
Section: Introductionmentioning
confidence: 71%
“…The amount of OTA in South African feeds (70-80 μg/ kg) from farms with nephropathy problems was significantly less than that presented as the explanation for Danish mycotoxic porcine nephropathy (MPN) (Krogh 1976;Krogh et al 1974). It seems, therefore, that South African porcine nephropathy may have a multitoxic aetiology because it cannot be explained by the concentration of OTA alone, and the conventional explanation appropriate for northern latitudes does not seem to apply.…”
Section: Introductionmentioning
confidence: 71%
“…OTA has been shown, in a variety of animal studies, to cause renal cancer and lifetime exposure to OTA induced renal adenomas or carcinomas in male Fisher-344 rats (NTP 1989). OTA can also cause decreased kidney function at just 8 μg/kg bw/day in female swine (Krogh et al 1974). While the renal system is the main target for OTA toxicity, adverse effects have been observed in other organs; such as cardiac and hepatic histological abnormalities (Hagelberg et al 1989), gastro-intestinal tract and lymphoid tissue lesions, intestinal fragility and kidney lesions (Elling et al 1975), and immunotoxic effects (Bondy and Pestka 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Australian broiler chickens (3 weeks of age) fed 1 mg/kg for 5 weeks were not adversely affected (Reichmann et al 1982). Other studies have reported reduced growth and also reduced egg production in chickens exposed to 0.5-1 mg/kg feed (Huff et al 1975;Krogh et al 1976;Prior and Sisodia 1978;Page et al 1980). A guidance level of 0.1 mg/kg DM is suggested for poultry.…”
Section: Aflatoxinsmentioning
confidence: 90%